A transfer of training evaluation study: investigating differences between goal setting and relapse prevention - Guardiola, Robert, author; Cleveland, Jeanette N., advisor (Colorado State University. Libraries, 2000)
This study assessed the effects of transfer of training methods on task performance and self-efficacy. One hundred fifty four participants were trained on how to complete a personal web page via three transfer of training methods: relapse prevention, goal setting, and a control condition (no transfer of training method). In addition, two levels of task complexity were varied between participants, giving the study a 2 X 3 between subjects design. The results showed no significant main effect for training method on a rated performance, including number of days to complete the task and percentage of required elements completed. There was a significant task complexity main effect, indicating that task complexity was shown to influence whether or not participants completed their web pages, and the percentage of required elements contained within the page. Finally, an interaction between task complexity and training method was found on self-efficacy. Specifically, there was a significant difference between the simple task - relapse prevention group and the complex task - relapse prevention group on changes in self-efficacy. Implications and suggestions for future research are discussed.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Transfer of training